Pemanfaatan Karbon dari Bunga Cemara Laut (Casuarina equisetifolia) untuk Penjernihan Minyak Jelantah - Rahmi, Maulidia Arsyta; Putra, Ananda; Sari, Trisna Kumala; Pernadi, Niza Lian; Istiqamah, Siti Sarah; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Used cooking oil is waste oil that has been used many times and is also known as used cooking oil which contains food residue and is a pollutant to the environment. This oil contains free fatty acids, carbonyl compounds, and peroxides. The content contained in used cooking oil can cause poisoning in humans and cause pollution to the environment. This study aims to clarify used cooking oil so that it can be reused. Carbon from sea pine flowers is used as a solution to clarify used cooking oil in this study. BCL carbon was obtained using the calcination method at various temperatures of 250oC, 300oC, 350oC, and 400oC. The resulting carbon is then subjected to a proximate test. Based on the results of the proximate test, the results obtained were in accordance with the SNI 06-3730-1995 standard with the optimum value obtained at 350oC calcination temperature. The clarification of used cooking oil is carried out by mixing used cooking oil and carbon as a result of calcination at 350ºC. Variations in the mass of carbon used are 1,3 and 5 grams. The results showed that the carbon of sea cypress flowers can be used as an absorbent for cleaning used cooking oil which can adsorb its fatty acid content. The optimum absorbent of this study was the 5g CBCL sample. This is evidenced by the results of the analysis that has been carried out with the lowest density value of 0.83 g/mL, the highest flow rate value of 4.312 mL/s and the lowest acid number value of 0.5 mg KOH/g.